PENGARUH KOMBINASI LATIHAN DUMBBELL WRIST CURL DAN MARYLAND 5 SPOT SHOOTING DRILL TERHADAP HASIL 3 POINT SHOOTING - Juniansyah, Hendias; Hartati, Hartati; Usra, Meirizal (Dharmas Education Journal (DE_Journal), 2023)
The purpose of this study was to determine the influence of a combination of dumbbell wrist curl exercises and maryland 5 spot shooting drill on the 3 point shooting results of basketball extracurricular students at SMA Negeri 1 Palembang and the magnitude of the influence. This study used a pre-experimental research design with a one group pretest-posttest design. The population in this study were all 25 basketball extracurricular students at SMA Negeri 1 Palembang. The sampling technique in this study was total sampling or saturated sampling so that the sample used was 25 people. The implementation of the research is the form of physical exercise was carried out 16 times within a period of one month. The data analysis technique using the t test for two dependent samples (paired samples) gives the result that is t count = -8.497 > t table = -2.064 and the value is ????????????. (2 − ????????????????????????) = 0.0000 < ???? = 0.05 then Ho is rejected thus giving the conclusion that there is an influence of a combination of dumbbell wrist curls and maryland 5 spot shooting drill on the 3 point shooting results of basketball extracurricular students at SMA Negeri 1 Palembang. The influence of the combination of dumbbell wrist curl and Maryland 5 spot shooting drill on the 3 point shooting results of basketball extracurricular students at Palembang 1 Public High School was 0.2827 in the moderate category.